The Influence of Digital Literacy, Interpersonal Trust, and Innovation Culture on Employee Adaptability: An Empirical Study of Digital Agriculture Startups in Indonesia - Sutopo; Sudianto (Universitas Airlangga, 2026)
Objective: This study aims to empirically investigate the influence of digital literacy, interpersonal trust, and innovation culture on employee adaptability, with a specific focus on digital agriculture startups in Indonesia. Design/Method/Approach: Data were collected through an online survey of 432 permanent employees working at various digital agriculture startups in Indonesia with at least one year of work experience. Data analysis was conducted using structural equation modeling (SEM) with Lisrel 8.8 software to examine the relationships between variables. Findings: The results of this study indicate that digital literacy, interpersonal trust, and a culture of innovation each have a positive and significant influence on employee adaptability. Employees who integrate digital skills with high levels of social trust in an innovative work environment are better able to navigate the dynamics of work in the digital agriculture sector. Originality/Value: This research provides a contextual contribution by exploring the synergy between digital literacy and interpersonal trust within the specific ecosystem of agricultural startups. Unlike studies in the general technology sector, this research examines the adaptability mechanisms at the intersection of the fundamental agrarian sector and the national digital economy. Rather than proposing a new theory, this study demonstrates how these established mechanisms operate at the intersection of the traditional agrarian sector and the modern digital economy, offering practical insights into the socio-technical challenges of digital transformation in emerging markets. Practical/Policy Implications: Digital agriculture startup leaders are advised to strengthen digital literacy programs and build a social safety net through employee trust to support a culture of innovation. This strategy is essential to ensuring organizational sustainability amid the complexities of integrating traditional agricultural technology and digital business systems in Indonesia.